Hypercarotenemia in Anorexia Nervosa Patients May Influence Weight Balance: Results of a Clinical Cross-Sectional Cohort Study - Lackner, Sonja; Meier-Allard, Nathalie; Mörkl, Sabrina; Müller, Wolfram; Fürhapter-Rieger, Alfred; Mangge, Harald; Zelzer, Sieglinde; Holasek, Sandra (Frontiers in Psychiatry, 2021)
Introduction: Anorexia nervosa (AN) can co-occur with hypercarotenemia, a clinical condition characterized by elevated β-carotene in plasma and skin tissue. Carotenoids have known anti-obesogenic effects in adipocyte biology. Thus, carotenoids may potentially play a retarding role in weight gain during the recovery of AN patients. This study evaluated the plasma carotenoid profile and subcutaneous adipose tissue (SAT) in a cohort of AN patients and normal weight (NW) controls. Methods: Plasma concentrations of α-carotene, β-carotene, β-cryptoxanthin, and lycopene were determined by HPLC analysis. SAT thicknesses were measured by a highly accurate and reliable ultrasound technique. Information on dietary intakes were collected by repeated 24-h recalls. Results: Sixty-two females (AN: n = 18, NW: n = 44) were included. The concentrations of β-cryptoxanthin (p = 0.045) and lycopene (p = 0.004) were significantly lower in AN patients. β-carotene levels were higher in AN patients (n.s.) and α-carotene did not differ significantly. SAT thickness was significantly lower in AN patients compared to controls (p < 0.001). β-carotene was significantly negative (rs = −0.471) and lycopene significantly positive (rs = 0.366) correlated with SAT. The correlation of β-carotene and SAT was even higher in the AN group alone (rs = −0.742). Also, β- cryptoxanthin and the sum of provitamin A carotenoids were correlated to SAT (rs = −0.647 and rs = −0.746, respectively) in AN patients. Fruits and vegetable intake did not differ significantly between AN and NW but adjusted for SAT, AN patients consumed relatively higher amounts (p = 0.006). Conclusion: Higher plasma β-carotene concentrations were associated with reduced SAT levels, most probably due to a reduced ability of the remaining adipose tissue to store carotenoids. Thus, the antiobesity effects of carotenoids might impact the treatment success of undernutrition and AN. A systemic carotenoid overload may contribute to changes in adipogenesis and metabolic capacities for energy storage. Therefore, high plasma β-carotene may be a marker of delay in weight recovery in AN patients. Interventional studies should consider including carotenoid-status in AN treatment.